WIRELESS NETWORK STUDY AND ANALYSIS USING NS2 SIMULATOR - Xiang, Chao (My University, 2008)
NS2 (Network Simulation version 2) is a well-known generic network simulator. Unlike other expensive simulation software, it is free and based on open source. It is widely used to simulate and emulate communication networks. Furthermore, it has a rich library of network and protocol objects, which almost involve most of the aspects of network technology. This makes NS2 the most favorable simulation software which is widely used in academic research. On the other hand, the results of the simulation are validated by many research centers. For this reason many published articles about network technology show their results by using NS2 simulation. Additionally, act an excellent instruction tool NS2 is widely utilized in education. Nowadays, NS2 becomes more and more popular in scientific research and education. Nevertheless, NS2 is quite difficult to handle for a beginner. Some reasons are: the content of NS2 is very huge; the official NS manual is not updated regularly and a lot of relative knowledge and tools are involved to operate NS2 efficiently. NS2 will be one of the main tools in the research activities of the Telecommunication Engineering Group (TEG). Hence, the main target of this thesis is to study NS2 deeply and to show how to construct an emulation environment by using NS2 and MATLAB. Different simulators are given to demonstrate how to proceed with NS2. This thesis will be one reference for TEG researches for the applications of NS2.
Keywords: NS2; Simulation; Integration; Emulation; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|